The Whitney Clinic - Donnelly, Anne Cohn; Scott, Walter; Shaw, Kathy; Gong, Millie; Morris, Lydia; Roark, Michael (London : SAGE Publications Ltd, 2017)
This case describes a community-based healthcare clinic and the issues facing the management and board of directors. The issues raised are common problems faced by all types of nonprofit organizations: insufficient fundraising and marketing policies to guide board decision making, confusion over staff and board roles in decision making, poorly thought-out bylaws that contribute to the confusion over board and staff roles, the challenge of harnessing the diverse backgrounds and opinions of a community-based board of directors, and lack of sound financial planning.
Originally published: Donnelly, A. C., Scott, W., Shaw, K., Gong, M., Morris, L., & Roark, M. (1996). The Whitney Clinic. 5-208-255. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Whitney Clinic; Nonprofit organizations -- Management -- Case studies; Communication in management -- Case studies